Effects of the Coastal Uplift on the Kuroshio Ecosystem, Eastern Taiwan, the Western Boundary Current of the North Pacific Ocean - Chen, Chung-Chi; Lu, Chun-Yi; Jan, Sen; Hsieh, Chih-hao; Chung, Chih-Ching (Frontiers in Marine Science, 2022)
The Kuroshio is the western boundary current of the North Pacific Ocean. In the subtropical region of eastern Taiwan, a coastal uplift of the isotherms has occurred. To explore its impact on this oligotrophic ecosystem, hydrographic data along the transect line at 23.75°N were measured between September 2012 and September 2014. Results show that the intensity of coastal uplift was positively correlated to the flow volume transport of the Kuroshio. Significant dissolved inorganic nutrients were uplifted to the sunlit zone, especially in the onshore. For example, compared to the offshore, nitrate concentration increased 0.49 μM (or ∼178%) in the upper 100 m of the onshore. The increased nutrients thereafter enhanced the growth of phytoplankton; for instance, the Chl a concentration increased 88.3%, compared to offshore, in the upper 100 m of the onshore. Phytoplankton community was mostly composed of picophytoplankton (<2 μm in size), which were dominated, in terms of relative abundance, by Prochlorococcus (83.6%), followed by Synechococcus (13.8%) and picoeukaryotes (2.7%). The relative abundance of Prochlorococcus increased from onshore toward offshore, but the trend was reversed for Synechococcus and picoeukaryotes, which may be affected by the coastal uplift. The results also suggest that the coastal uplift may support more energy transferred to higher tropical levels in this oligotrophic Kuroshio ecosystem.